Imaging of the Antarctic ionosphere: Experimental results - P. Yin; C.N. Mitchell; L. Alfonsi; M. Pinnock; P. Spencer; G. De Franceschi; V. Romano; P. Newell; P. Sarti; M. Negusini; CAPRA, Alessandro (Journal of Atmospheric and Solar-Terrestrial Physics, 2009)
Ground-based dual-frequency GPS observations can be used to create images of electron density. This is well established for the Arctic ionosphere; here one of the first results is presented for the Antarctic. In this study, the GPS receivers in the Antarctic are supplemented with another GPS receiver onboard CHAMP. The aim of the study is to demonstrate the technique for investigating geophysical events, for example, an ionospheric disturbance period on 11 February 2004. The images have been validated by in-situ measurements from DMSP and CHAMP satellites, as well as Super Dual Auroral Radar Network (SuperDARN) convection patterns, which are able to confirm the location, presence, and transportation of large-scale plasma patches. This study indicates that although the convection still dominates in the high-latitude ionosphere, soft precipitation within the polar cap may play a role in the evolution of the polar patches. It also illustrates the potential for future multi-instrument studies of the Antarctic. (C) 2009 Elsevier Ltd. All rights reserved.